Mechanical, thermal properties and stability of high renewable content liquefied residual biomass derived bio-polyurethane wood adhesives. (September 2020) - Jasiūnas, Lukas; Peck, Gabrielle; Bridžiuvienė, Danguolė; Miknius, Linas
Abstract: Bio-polyurethane adhesives ( bio-PU ) of high renewable content ( up to 87% ) were produced using biomass biopolyols obtained previously via crude-glycerol mediated solvothermal liquefaction of three industrial biomass residue feedstocks: digested sewage sludge, hemp stalk hurds and sugar beet pulp, and commercial pentamethylene diisocyanate. The produced adhesives were capable of exhibiting tensile strength values within the threshold of two commercially available polyurethane ( PU ) wood adhesives ( 5.77–11.03 MPa ) . Varying biomass feedstock particle size and dry matter content, adhesive formulation isocyanate to hydroxyl group ratios and biomass biopolyol blending with blank crude glycerol biopolyol showed varying effects on the adhesives produced. Although bio-PU adhesives exhibited lower thermal stability, the non-flame retarded adhesives showed lower potential for fire spread and nearly identical flammability with lower heat release rates in the cone calorimeter. In terms of fire toxicity, biopolyol adhesives were found to be less toxic in well-ventilated flaming fire scenarios, with significantly lower smoke and CO production than the commercial formulation. However, both commercial and biopolyol adhesives yielded significant quantities of CO and HCN toxicants when tested in under-ventilated and post-flashover fire scenarios. Here, the tested bio-PU bound wood system exhibited 25–30% higher fractional effective doses compared to the commercial PU adhesive analogue. The biopolyol adhesives were much more hydrophilic ( water uptake of up to 119% ), less stable dimensionally ( max. elongation of 3% ), contained significantly more water soluble components ( up to 43% ), and biodegraded at higher rates ( up to 0.89%/month ), compared to commercial PU. They were, nonetheless, hydrolytically stable as their tensile strengths did not decrease below levels after water soaking and drying. Overall, the adhesives produced show promise as sustainable alternatives in applications where high thermal stability and low water uptake are not crucial parameters.